The fiancée : a novel - White, Kate, 1950- (Harper, an imprint of HarperCollinsPublishers, 2021)
Sensing that something is off with her brother-in-law's new fiancée, Hannah, who is a fellow actress, Summer, finding her suspicions ignored, investigates just how far Hannah is willing to go to keep her perfect image intact when a family member is murdered.